Management and implications of severe COVID-19 in pregnancy in the UK: data from the UK Obstetric Surveillance System national cohort - Vousden,N; Ramakrishnan,R; Bunch,K; Morris,E; Simpson,N; Gale,C; O'Brien,P; Quigley,M; Brocklehurst,P; Kurinczuk,JJ; Knight,M (Acta Obstetricia et Gynecologica Scandinavica, 2022)
INTRODUCTION: There is a lack of population level data on risk factors and impact of severe COVID-19 in pregnancy. The aims of this study were to determine the characteristics, and maternal and perinatal outcomes associated with severe COVID-19 in pregnancy compared with those with mild and moderate COVID-19 and to explore the impact of timing of birth. MATERIAL AND METHODS: This was a secondary analysis of a national, prospective cohort study. All pregnant women admitted to hospital in the UK with symptomatic SARS-CoV-2 from March 1, 2020 to October 31, 2021 were included. The severity of maternal infection (need for high flow or invasive ventilation, intensive care admission or died), pregnancy and perinatal outcomes, and the impact of timing of birth were analyzed using multivariable logistic regression. RESULTS: Of 4436 pregnant women, 13.9% (n = 616) had severe infection. Women with severe infection were more likely to be aged ≥30 years (adjusted odds ratio [aOR] aged 30-39 1.48, 95% confidence interval [CI] 1.20-1.83), be overweight or obese (aOR 1.73, 95% CI 1.34-2.25 and aOR 2.52 95% CI 1.97-3.23, respectively), be of mixed ethnicity (aOR 1.93, 95% CI 1.17-3.21) or have gestational diabetes (aOR 1.43, 95% CI 1.09-1.87) compared with those with mild or moderate infection. Women with severe infection were more likely to have a pre-labor cesarean birth (aOR 8.84, 95% CI 6.61-11.83), a very or extreme preterm birth (28-31+ weeks' gestation, aOR 18.97, 95% CI 7.78-14.85; <28 weeks' gestation, aOR 12.35, 95% CI 6.34-24.05) and their babies were more likely to be stillborn (aOR 2.51, 95% CI 1.35-4.66) or admitted to a neonatal unit (aOR 11.61, 95% CI 9.28-14.52). Of 112 women with severe infection who were discharged and gave birth at a later admission, the majority gave birth ≥36 weeks (85.7%), noting that three women in this group (2.7%) had a stillbirth. CONCLUSIONS: Severe COVID-19 in pregnancy increases the risk of advers